Modelo de gestión por competencias y su contribución al buen servicio del registro civil, identificación y cedulación del cantón Babahoyo - Loor Rivera, Yuliana Rosalia (2015)
This research focuses on the factors preventing improve customer service will be held at the Civil Registry and Identification of Canton Babahoyo Rivers Province. Given the characteristics of a non- experimental research was implemented as it will not be built any situation they observe existing situations in the Civil Registry and Identification , unintentionally caused by the researcher , the phenomenon as it is presented will be observed ; in our research independent variables have already occurred and cannot be manipulated...